ADVENT OF THE GRAPHIC NOVEL: A NEW GENRE OF LITERARY REPRESENTATION - Anuradha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
While specialists in literature are now giving more serious attention to various forms of popular culture, much of the current research remains limited to historical overviews or thematic studies. This becomes evident when trying to critically analyze newer phenomena, such as the graphic novel. The term Graphic Novel was first introduced by Will Eisner in 1978 to describe his comic book collection, A Contract with God. Steve Roiteri defines a graphic novel as a standalone story in comics form, published as a book. This definition sets the graphic novel apart from the comic book, which is typically a short magazine, about 32 pages long, published serially with a soft cover and on inexpensive paper. Traditionally, comic books have been very affordable and primarily targeted at children and adolescents, although they are not exclusively read by them.